KEDUDUKAN DAN TANGGUNG JAWAB PERUSAHAAN MULTINASIONAL (MNC) DALAM HUKUM INTERNASIONAL - Lila Sitha Rambisa; Ni Made Suksma Prijandhini Devi Salain (Kertha Negara : Journal Ilmu Hukum, 2013)
Free Trade Agreements attract many Multi National Corporations (MNCs) to invest inother countries. The economic impact of MNCs, made some difficulties to developingcountries in enforcing national laws. This condition brings international law to try tofill the gap when the national law failed to make MNCs to responsible for damagecaused by activities of the company. But the fact that MNCs do not have legalpersonality under international law has become the main obstacle in theimplementation of international law This paper is intended to discuss the MNC statusunder international law, and analysis how efforts of International Law in the impositionof liability for Multi National Corporations.